The Influence of Cooperative Integrated Reading Composition (CIRC) Learning Towards the Reading Comprehension Ability of Third Grade Elementary School Students - Dhea Ayu Fitri; Kurniaman, Otang; Zufriady (Yayasan Thaifah Manshurah Pekanbaru, 2023)
This study aims to determine reading comprehension skills before and after applying the Cooperative Integrated Reading Composition (CIRC) method. This type of research is quantitative with the type of Nonquivalent Group Design, namely there are two groups, namely the control group and the experimental group which are not randomly selected. This research was conducted at SDN 005 Hangtuah class III with a total of 70 students, namely class III A students 35 students and III B 35 students. Based on the results of the study, it was found that the average score in the experimental class before the treatment (pretest) was 48.54, while the average score in the experimental class after the treatment (posttest) was 70.71, and the average score experimental n-gain of 0.44 which is the medium category,as well as the results of hypothesis testing using independent t-test with t hitung equal to = 4.302 and t tabel equal to = 1.995 then it can be concluded t hitung > t tabel then H0 is rejected and H1 is accepted, meaning it is significant. This means that there is an influence on the reading comprehension ability of third grade students at SDN 005 Hangtuah between the initial pretest and the final posttest using the Cooperative Integrated Reading Composition method. This shows that using the Cooperative Integrated Reading Composition method has an effect on the reading comprehension ability of third grade students at SDN 005 Hangtuah